DESKRIPSI KEMAMPUAN MAHASISWA PENDIDIKAN KIMIA DALAM MENYELESAIKAN SOAL HOTS PADA MATERI ASAM BASA - Pratiwi, Fitri; Enawaty, Eny; Rasmawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study was to describe  the ability of students to solve HOTS questions on acid-base material and what factors influence students in solving HOTS questions on acid-base material. The form of research uses descriptive research. The research sample was FKIP Tanjungpura University. Chemistry education students in the 6th semester were 58 students. The ability of chemistry education students to solve hots questions was measured using essay written tests, and unstructured interviews. The research instrument was validated using the Gregory test matrix. The results showed that the ability of chemistry education students to solve hots was classified as moderate. This are indicated by the moderate percentage of the indicator at 69.2%. This proves the ability of chemistry education for each indicator are high. Factors affecting the ability of students are the lack of understanding the Bronsted-Lowry concept, not understanding the formula of vinegar acid levels and the difficulty in describing the strong acid and strong base titration curves.Keywords: The Ability, High Order Thinking Skill, Acid-Base Material